2008
DOI: 10.1124/mol.108.046615
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants for the Activating/Blocking Actions of the 2H-1,4-Benzoxazine Derivatives, a Class of Potassium Channel Modulators Targeting the Skeletal Muscle KATP Channels

Abstract: The 2H-1,4-benzoxazine derivatives are modulators of the skeletal muscle ATP-sensitive-K ϩ channels (K ATP ), activating it in the presence of ATP but inhibiting it in the absence of nucleotide. To investigate the molecular determinants for the activating/blocking actions of these compounds, novel molecules with different alkyl or aryl-alkyl substitutes at position 2 of the 1,4-benzoxazine ring were prepared. The effects of the lengthening of the alkyl chain and of branched substitutes, as well as of the intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 27 publications
(44 reference statements)
0
17
0
Order By: Relevance
“…A conformational analysis showed that the planar area of the 2H-1,4-benzoxazines overlaps that of the adenine nucleotide tri-and diphosphates. The electronic distribution profile of this area is also similar to that of the adenine nucleotides, which were reached by electrons; this result suggests that these compounds share a common ATP/ADP interaction interface on the receptor sites (Tricarico et al, 2008). No data are available regarding the effects or possible dual actions of these nucleotide analogs on the pancreatic ␤ cell KATP channel or glucose disposal in normal mice.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…A conformational analysis showed that the planar area of the 2H-1,4-benzoxazines overlaps that of the adenine nucleotide tri-and diphosphates. The electronic distribution profile of this area is also similar to that of the adenine nucleotides, which were reached by electrons; this result suggests that these compounds share a common ATP/ADP interaction interface on the receptor sites (Tricarico et al, 2008). No data are available regarding the effects or possible dual actions of these nucleotide analogs on the pancreatic ␤ cell KATP channel or glucose disposal in normal mice.…”
Section: Introductionmentioning
confidence: 82%
“…A biphasic behavior was observed in the glucose disposal curves that were determined in vivo after the administration of increasing doses of the 2-nhexyl analog; these data can be explained by accounting for the opposite in vitro effects of this compound on pancreatic ␤ cells and skeletal muscle KATP channels (Fig. 9) (Tricarico et al, 2008).…”
Section: Downloaded Frommentioning
confidence: 98%
See 3 more Smart Citations